Meningkatkan Motivasi Belajar Matematika Kelas 1 SD Islam Alam Bunayya Melalui Model Pembelajaran Kooperatif Tipe Make A Match - Sholichah, Miftahul; Wahyuni, Akhtim (MODELING: Jurnal Program Studi PGMI, 2023)
This study aims to increase the motivation to learn mathematics in grade 1 elementary school students who are in a period of transition and adaptation to learning situations between kindergarten and elementary school levels through the application of the Make a Match cooperative learning model. This research is a Classroom Action Research (CAR) which was carried out at SDI Alam Bunayya, Prambon sub-district, with research subjects in class I semester 1 of the 2022/2023 academic year, totaling 16 students. This study used interviews, observation and documentation with descriptive qualitative data analysis. In this study, the results of high mathematics learning motivation in the implementation of the action, the level of motivation to learn mathematics showed progress in each cycle, from the pre-cycle which was only 19% and in the first cycle it increased by 56.25%. However, these results still do not meet the specified action achievement indicators, so it is necessary to carry out further actions in cycle II. Whereas in cycle II the level of student learning motivation increased by 87.5%, these results have reached a high level of learning motivation exceeding the achievement indicators of the actions applied by 80%. So it can be concluded that the cooperative learning model of the Make a Match type is proven to be able to increase students' motivation to learn mathematics.